The Development of Teachers’ Epistemic Beliefs about Science: A Review of the Literature - Ellen Watson; Sarah Ragoub (Studies in Philosophy of Science and Education, 2025)
Empirical research studies investigating teachers’ epistemic beliefs about science are scattered across the science education literature. This research summarizes and describes the literature investigating the development of teachers’ epistemic beliefs about science over the last 25 years. The focus of this summary is on how teachers’ epistemic beliefs about science have been investigated and conceptualized as well as the themes arising from empirical studies considering this construct. Using a systematic literature review (PRISMA protocol), empirical research studies investigating the development of teachers’ epistemic beliefs about science were identified. Thematic analysis was used to analyze, summarize, and interpret data. Findings indicate that teachers’ epistemic belief development is commonly studied using interventions to instruct teachers about and engage them with the epistemic underpinnings of science. The nature of science was the most frequently used framework to conceptualize teachers’ epistemic beliefs about science, with few studies using approaches more common in the general epistemic belief or epistemic belief development literature. Reflections on and interpretations of the summary of this systematic literature are provided, including potential considerations for future directions of research investigating the development of teachers’ epistemic beliefs about science.